2019
DOI: 10.1007/s13239-019-00431-4
|View full text |Cite
|
Sign up to set email alerts
|

Location-Specific Comparison Between a 3D In-Stent Restenosis Model and Micro-CT and Histology Data from Porcine In Vivo Experiments

Abstract: BackgroundCoronary artery restenosis is an important side effect of percutaneous coronary intervention. Computational models can be used to better understand this process. We report on an approach for validation of an in silico 3D model of in-stent restenosis in porcine coronary arteries and illustrate this approach by comparing the modelling results to in vivo data for 14 and 28 days post-stenting.MethodsThis multiscale model includes single-scale models for stent deployment, blood flow and tissue growth in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(50 citation statements)
references
References 57 publications
1
49
0
Order By: Relevance
“…In animal studies on coronary stents, significant differences in lumen area were found between the fringes and mid segments at 1M, 31 or along the stented region at 14 days post-intervention. 35 The present work proves the importance of observing the entire remodeling trajectory of ISR in human arteries, by focusing on human stented SFAs. No longitudinal data on ISR in human stented SFAs are currently available to be directly compared with the findings of the present study.…”
Section: Morphological Progressionmentioning
confidence: 74%
See 1 more Smart Citation
“…In animal studies on coronary stents, significant differences in lumen area were found between the fringes and mid segments at 1M, 31 or along the stented region at 14 days post-intervention. 35 The present work proves the importance of observing the entire remodeling trajectory of ISR in human arteries, by focusing on human stented SFAs. No longitudinal data on ISR in human stented SFAs are currently available to be directly compared with the findings of the present study.…”
Section: Morphological Progressionmentioning
confidence: 74%
“…Similar considerations are valid for animal studies related to ISR in coronary arteries, characterized by a short follow-up period (2 weeks or 1M). 6,25,35 A similar approach to morphological analysis was applied in a previous longitudinal study quantifying the lumen remodeling trajectory over 1Y follow-up period in patients treated with infra-inguinal veingraft. 15 A direct comparison between the lumen remodeling trajectories is not possible because the biological processes leading to ISR in stented SFAs and restenosis in vein grafts are different.…”
Section: Morphological Progressionmentioning
confidence: 99%
“…On the other hand, the model gives a reasonable prediction for the behaviour of untreated ECs and should provide a reasonable scenario of endothelium regeneration for a bare metal stent (BMS). This allows it to be used as a part of multiscale models of restenosis in BMS, such as the one described in Zun et al (2017Zun et al ( , 2019.…”
Section: Discussionmentioning
confidence: 99%
“…Coupled with FE analysis, the ABM was adopted by Keshavarzian et al ( 2018 ) to model the response of vessels to the levels of growth factors, proteases, signalling molecules and blood pressure. The ABM was also applied for multiscale modelling of stent deployment, and subsequent blood flow and tissue growth in a stented vessel (Tahir et al 2013 , 2015 ; Zun et al 2019 , 2017 ), in agreement with in vivo post-stenting data. On the other hand, Holzapfel et al ( 2000 , 2002 ) developed a three-dimensional model for simulation of balloon angioplasty and stent deployment in a stenotic artery to gain a mechanistic understanding of the PCI procedure.…”
Section: Introductionmentioning
confidence: 85%